[Urban] anchoring of Retreat Road: The contribution of a [transverse connector] into an urban development corridor - Beetul, Sajjiv Ashvind (School of Architecture, Planning and Geomatics, 2014)
This dissertation investigates the urban anchoring of Retreat Road in the Southern Suburbs as a potential transverse connector for the metropolitan urban corridor around Main Road linking Central Cape Town and the Southern Suburbs in the Western Cape of South Africa. Its close proximity to Main Road makes it into a potential transverse connector providing energy and life to that portion of the metropolitan urban corridor. Even though showing great promise as a possible localised activity strip, the development of Retreat Road seems to have been frozen in time. The awkward geometry of the connection of Retreat Road to Main Road is one of the main causes of this stagnation. To facilitate the flow of energy, this dissertation proposes the realignment of Retreat Road, thus giving birth to a New Retreat Road while at the same time keeping the Old Retreat Road. This new simple geometry also provides the possibility of creating a gateway for Retreat Road on Main Road. Urban anchoring of Retreat Road is investigated through an urban design strategy of a properly structured public realm. Theory along the lines of Dynamic City, The Capital Web and Neo-Rationalism was very useful in understanding the incremental, catalytic and complex nature of urbanism and subsequently the notion of public anchoring. Various case studies and precedents, local ones as far as possible, were consulted with a view to understand the practical application of theory. A significant conclusion drawn from this investigation is that a transverse connector is very crucial in aiming to achieve integration between an urban corridor and the surrounding tissue falling short of the corridor. Transverse connectors are usually associated with nodes or cores of high energy in a corridor. Usually, these cores situate themselves around or next to a transport interchange as an urban anchoring element.